«Հասարակական կազմակերպություն» հասկացության սահմանումն ու կայացման իրավական հիմքերը - Ստեփանյան, Լիլիթ (YSU Journal of International Affairs, 2016)
In the political life of modern society needs and interests of citizens can not be realized only through the institutions of the state or politicalparties. In the process of implementation of these demands, the important role played citizens' associations - non-governmental organizations, associations, charitable organizations, etc. For the political modernization in the country, active horizontal ‘waves’ are very important. These ''waves'' for smaller and flexible resources implements civil society: the world enters a new stage of social and political relations, changing issues on the political agenda of the day and the national security of the country stopped be only care of the state.
Keywords: Civil society, constitutional state, the institutions of the social system, the political structures of state, non-governmental organization, social-political dialogue, political culture